2022
DOI: 10.3390/nano12234222
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Nanoplastic Particles Enhances Acinetobacter Survival, Biofilm Formation, and Serum Resistance

Abstract: The interaction between nanoplastics and bacteria remains still largely unclear. In this study, we determined the effect of nanopolystyrene particle (NP) on a bacterial pathogen of Acinetobacter johnsonii AC15. Scanning electron microscopy (SEM) analysis indicated the aggregation of NPs from 10 μg/L to 100 μg/L on surface of A. johnsonii AC15, suggesting that A. johnsonii AC15 acted as the vector for NPs. Exposure to 100–1000 μg/L NPs increased the growth and colony-forming unit (CFU) of A. johnsonii AC15. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Indirect ingestion of nanoplastics can occur through ingesting natural prey with nanoplastics adsorbed on the prey cell. Tang et al (2022) reported the penetration of nanoplastic particles into bacterial cells across the cell envelope, with nanoparticles accumulating inside the bacterial cells. The same authors observed a large number of 100 nm nanoplastic particles adsorbed and aggregated on the surface of Acinetobacter johnsonii AC15, which significantly increased the growth of bacteria, while Dai et al (2022) observed 80 nm sized positively charged polystyrene embedded into the cell envelope of Escherichia coli with no apparent effect on the bacterial cell.…”
Section: Ingestion Of Microplastics and Nanoplastics By Ciliated Micr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Indirect ingestion of nanoplastics can occur through ingesting natural prey with nanoplastics adsorbed on the prey cell. Tang et al (2022) reported the penetration of nanoplastic particles into bacterial cells across the cell envelope, with nanoparticles accumulating inside the bacterial cells. The same authors observed a large number of 100 nm nanoplastic particles adsorbed and aggregated on the surface of Acinetobacter johnsonii AC15, which significantly increased the growth of bacteria, while Dai et al (2022) observed 80 nm sized positively charged polystyrene embedded into the cell envelope of Escherichia coli with no apparent effect on the bacterial cell.…”
Section: Ingestion Of Microplastics and Nanoplastics By Ciliated Micr...mentioning
confidence: 99%
“…Importantly, smallersized nanoparticles of ≤ 10 nm can easily penetrate the cell membrane (Frankel et al, 2020;Liu et al, 2023). The translocation through the cell membrane is determined by the surface charge of the particle; positively charged particles display more favorable electrostatic interactions with bacterial membranes than negatively charged particles (Tang et al, 2022). Indirect ingestion of nanoplastics has been reported for filter-feeding invertebrates such as D. magna, which ingested Chlamydomonas reinhardtii with nanoplastic particles of 51 nm attached to the surface of the algal cell (Chae et al, 2018).…”
Section: Ingestion Of Microplastics and Nanoplastics By Ciliated Micr...mentioning
confidence: 99%
“…Once bioavailable to organisms, nanoplastics could be further internalized in cells and transported to certain organelles, such as mitochondria [ 15 ]. Accompanied with bioavailability and accumulation, some adverse effects on the development and functions of organs or tissues could be observed in different organisms after nanoplastic exposure [ 16 , 17 , 18 , 19 ]. Nanoplastic toxicity could be induced at both exposed parental generations (P0-G) and their offspring [ 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…7 Largely owing to these facts, the environmental fate, transport, and risk of microplastics and nanoplastics have received increasing attention. [8][9][10][11][12][13] Through the food chain, nanoplastics are bioavailable to humans. 14,15 After ingestion, nanoparticles will encounter the intestinal barrier and then reach system circulation and other tissues.…”
Section: Introductionmentioning
confidence: 99%